Light Industry Technology of Chiral Perovskite Nanomaterials Construction and Photoelectric Properties. (21st September 2021) - Sun, Jie
Abstract : Perovskite nanomaterials have become a new research hotspot due to the many novel physical properties of quantum effects and have good application prospects in the field of optoelectronics. Among them, the realization of controllable fabrication of perovskite nanomaterials is the basis of performance studies and applications and is also a difficult point. Reducing production costs to improve manufacturing methods, further improve product controllability, promote advantages, or improve disadvantages will be very important for further application of perovskite nanomaterials. Therefore, this paper studies the construction of titanium ore nanomaterials by designing a novel preparation process and, at the same time, analyzes the related optoelectronic properties of the obtained materials. In this paper, a triangular PbI2 nanosheet having a uniform and controllable shape and size was successfully fabricated by physical vapor deposition through the introduction of a limited space, and related characterization was performed to show uniform controllability and high crystallinity. Using PbI2 nanosheets as the substrate, MAPbI3 nanosheets were further prepared and related characterizations proved that the obtained nanosheets had high crystallinity and excellent optical properties. The experiment proves that the peak position of the fluorescence spectrum obtained by Gaussian fitting is 800 nm and the half-peak width is about 45 nm. At the same time, MAPbI3 exhibits strong light absorption characteristics when the wavelength is less than 800 nm. This shows that this enclosed space deposition method can improve the uniformity and controllability of PbI2 and MAPbI3 nanosheet fabrication, which provides the basis for further research on MAPbI3 nanomaterials and references to the controllable growth of other nanomaterials.